2018
DOI: 10.1038/s41395-018-0381-4
|View full text |Cite
|
Sign up to set email alerts
|

Reasons For Lack of Follow-up Colonoscopy Among Persons With A Positive Fecal Occult Blood Test Result: A Qualitative Study

Abstract: Colorectal cancer (CRC) is the second leading cause of cancerrelated death worldwide [1]. CRC is amenable to early detection with earlier diagnosis improving prognosis [2-4]. Like many regions around the world, Canadian provincial screening programs use fecal occult blood tests (FOBTs)-guaiac or immunochemical, depending on the province-as the initial CRC screening test [5]. When FOBTs are positive (FOBT+), colonoscopy is required for a definitive CRC diagnosis [6]. Delays in obtaining follow-up colonoscopy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…Patient-and provider-related barriers were the most common reasons for lack of colonoscopy. Patient-level barriers included fear of the procedure and the bowel preparation and low priority, which is consistent with prior literature [12,22,29]. Provider-related reasons included lack of provider recommendation for colonoscopy, previously normal colonoscopy, or a repeated stool screening test that was normal.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Patient-and provider-related barriers were the most common reasons for lack of colonoscopy. Patient-level barriers included fear of the procedure and the bowel preparation and low priority, which is consistent with prior literature [12,22,29]. Provider-related reasons included lack of provider recommendation for colonoscopy, previously normal colonoscopy, or a repeated stool screening test that was normal.…”
Section: Discussionsupporting
confidence: 74%
“…Second, we were limited by our small sample size. However, to date, our study remains one of few to interview patients with an abnormal FIT and previous studies exploring patient perspectives are often small [29,33]. Third, our study was limited in its scope and relies on patient recollection of events, which may be susceptible to response bias, memory bias, or poor recall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the US Multi-Society Task Force on Colorectal Cancer recommends a colonoscopy completion target for FIT-positive individuals of at least 80% as a quality metric, 2 rates ranging from 50% to 63% have been reported. 3 FIT-positive individuals have at least a 3-fold higher risk of colorectal cancer (CRC) than those receiving screening colonoscopy, 2,4,5 and how quickly FIT-positive individuals need to undergo diagnostic colonoscopy is a key question with important implications for the patient and the health system providing that care. Corley et al 6 had previously reported that CRC risk increased when time to colonoscopy exceeded 10 months within an integrated US healthcare system, but until now, corroborating data were lacking.…”
mentioning
confidence: 99%
“…A recent qualitative study from Canada found that patient or provider belief that a positive fecal occult blood test was a false-positive result was the leading reason for lack of diagnostic colonoscopy. 3 Therefore, it seems reasonable to assume that asymptomatic FIT-positive individuals who initially defer colonoscopy because they believed it was a false-positive result may subsequently seek colonoscopy when symptoms develop. In the current study, it is plausible that a substantial proportion of participants who underwent colonoscopy more than 12 months after the positive FIT did so because they developed symptoms of cancer and not because they or their provider finally remembered to follow up the abnormal test.…”
mentioning
confidence: 99%